Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose we are given functors $F:\mathcal{C}\rightarrow\mathcal{D}$ and $G,G':\mathcal{D}\rightarrow\mathcal{C}$ such that $G$ and $G'$ are both right adjoint to $F$. To show that $G$ and $G'$ are isomorphic, we wish to come up with a natural isomorphism between the two functors. This is how Awodey does it:

For any $D\in\mathcal{D}$ and any $C\in\mathcal{C}$, we have that $Hom(C,GD)\cong Hom(FC,D)\cong Hom(C,G'D)$ simply using the hom-set definition of adjunctions. By the Yoneda principle, this means that $GD\cong G'D$ for all $D\in\mathcal{D}$.

Awodey then states that

But this isomorphism is natural in $D$, again by adjointness.

I dont' quite understand how the naturality follows from adjointness. Any help is appreciated.

share|cite|improve this question
up vote 11 down vote accepted

The bijection $\hom(C,GD) \cong \hom(C,G'D)$ is natural in $C$, thus it is induced by an isomorphism $GD \cong G'D$ (Yoneda Lemma). But it is also natural in $D$, and since the Yoneda embedding is faithful, this means that $GD \cong G'D$ is natural in $D$. More details:

If $D \to E$ is a morphism, then

$\begin{array}{ccc} GD & \rightarrow & G'D \\ \downarrow & & \downarrow \\ GE & \rightarrow & G'E \end{array}$

commutes iff for every $C$ the diagram

$\begin{array}{ccc} \hom(C,GD) & \rightarrow & \hom(C,G'D) \\ \downarrow & & \downarrow \\ \hom(C,GE) & \rightarrow & \hom(C,G'E) \end{array}$


share|cite|improve this answer
Thanks a lot for the clear-cut answer! – Sakif Khan May 13 '13 at 1:23

This seems to be one of those cases where the proof from scratch is the easy, and you don't need to know (explictly) anything about Yoneda.

1). You know there is a natural isomorphism given by $\varphi_{A,D} :$hom$(A,GD)\rightarrow $hom$(A,G'D)$

2). Set $A=GD$, $\varphi _{GD,D}(1 _{GD})=\tau _{D}$. Then, by what follows, the $\tau _{D}$ are the components of the required natural isomorphism $G\overset{\cdot }{\rightarrow}G'$

3) Write

\begin{array}{ccc} \hom(GD,GD) & \rightarrow & \hom(GD,G'D) \\ \downarrow & & \downarrow \\ \hom(GD,GD_{1}) & \rightarrow & \hom(GD,G'D_{1} ) \end{array} Then if $f:D\rightarrow D_{1}$, follow $1_{GD}$ around the square. This gives $G'f\circ \tau _{D}=\varphi _{GD,D_{1}}(Gf)$.

4). Write \begin{array}{ccc} \hom(GD_{1},GD_{1}) & \rightarrow & \hom(GD_{1},G'D_{1}) \\ \downarrow & & \downarrow \\ \hom(GD,GD_{1}) & \rightarrow & \hom(GD,G'D_{1} ) \end{array}

and follow $1_{GD_{1}}$ around the square. This gives $\varphi _{GD,D_{1}}(Gf)= \tau _{D_{1}}\circ Gf$

5). Combining the previous two items, you get $G'f\circ \tau _{D}=\tau _{D_{1}}\circ Gf$, so $\tau $ is a natural transformation. Now, since $\varphi$ is an isomorphism, natural in $A$ and $D$, for each $D$, $\varphi _{GD,D}(1 _{GD})=\tau_{D}$ is an isomorphism, which implies $\tau $ itself is.

share|cite|improve this answer

We actually have a composite of natural isomorphisms $\tau:\hom(\bullet,G\bullet)\to \hom(F\bullet,\bullet)\to \hom(\bullet,G'\bullet)$.

In more details, $\tau$ has components $\tau_{C,D}:\hom(C,GD)\to\hom(C,G'D)$ satisfying the naturality condition: for arrows $\gamma:C_1\to C$, $\ \delta:D\to D_1\,$ and $\, f:C\to GD$ we have $$\tau(G\delta\circ f\circ\gamma)=G'\delta\circ\tau(f)\circ\gamma\,. $$ Now applying the Yoneda lemma basically means to consider the case when $C=GD$ and apply $\tau$ to $1_{GD}$. It leads to a $GD\to G'D$ arrow, verify (using the above equation) that it's natural in $D$, and find its inverse (e.g. by applying the same to $C=G'D$ and $\tau^{-1}$.

share|cite|improve this answer
Yes, but I'm not quite sure how that implies that the isomorphism $GD\cong G'D$ is natural. – Sakif Khan May 12 '13 at 23:51
Thanks for the reference. – Sakif Khan May 13 '13 at 0:58

I don't sure that I answer precisely on your question, but I want to share my idea.

Let's view the category $C$ as a full subcategory of its presheaves(image of the Yoneda embedding $C\to\mathbf{Set}^{C^{op}}$).

Adjunction gives you a natural isomorphism $hom_C(C,G(D))\to hom_C(C,G'(D))$, which is actually a natural isomorphism between the following two functors: $$ X=(hom_C\circ(I_{C^{op}}\times G))\colon C^{op}\times D\to\mathbf{Set}; $$ $$ Y=(hom_C\circ(I_{C^{op}}\times G'))\colon C^{op}\times D\to\mathbf{Set}, $$ which are objects in the category $\mathbf{Set}^{C^{op}\times D}$. Consider an exponential functor: $$ E\colon\mathbf{Set}^{C^{op}\times D}\to(\mathbf{Set}^{C^{op}})^D $$ So we have two isomorphic functors $E(X),E(Y)\colon D\to\mathbf{Set}^{C^{op}}$. It's easy to check that their images are in $C$, and constriction on $C$ yields $E(X)|_C=G, E(Y)|_{C}=G'$. Thus, the natural isomorphism between $E(X)$ and $E(Y)$ induce a natural isomorphism between $G$ and $G'$.

share|cite|improve this answer
I think this is a nice answer. – Sakif Khan May 13 '13 at 0:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.